Critical Organ Dysfunction in Newborns with Gastroschisis - de la Cruz, Diomel; Kaufmann, Erin; Nicolas, Lara; Davoodi, Marjan; Wynn, James L.; Aziz, Khyzer (American Journal of Perinatology, 2025)
Gastroschisis is the most common newborn abdominal wall defect. Gastroschisis classification is based on the absence (simple gastroschisis [SG]) or presence (complex gastroschisis [CG]) of bowel morbidity. The severity of critical organ dysfunction with gastroschisis is unknown.This was a multicenter, retrospective cohort study of infants with gastroschisis (birth weight ≥ 1.8 kg and gestational age ≥ 35 weeks) admitted to the University of Florida Health NICU between January 1, 2012, and April 1, 2023, and the Johns Hopkins NICU between July 1, 2016, and December 31, 2024. All data was collected from the electronic health record. CG was defined as the presence of atresia, necrosis, perforation, volvulus, jejunostomy, resection, or short bowel syndrome. Hourly organ dysfunction was quantified by the neonatal sequential organ failure assessment (nSOFA) score (measures respiratory, cardiovascular, and hematologic dysfunction with a range from 0 to 15 [severe]).We identified 120 patients with gastroschisis (49% male; 90 with SG). Compared with patients with SG, neonates with CG had greater maximum nSOFA scores (median: 2 [IQR]: [0, 4] vs. 3 [1, 7]; p = 0.02). The coefficient of variation on cumulative nSOFA scores calculated at 24-hour intervals after birth as a measure of organ dysfunction heterogeneity for SG patients was 278 to 332% and was 216 to 266% for CG patients.This is the first high-granularity quantification of critical organ dysfunction in gastroschisis patients. We found a low overall severity of critical organ dysfunction among all patients. Substantial heterogeneity was present in both groups. The nSOFA may help to identify a subset of patients with critical organ dysfunction outside of bowel morbidity.
Keywords: neonate; gastroschisis; nSOFA; critical illness